Giant cell tumour of the femoral neck: Failure of curettage–cavity filling cementation with screw fixation, a case report. (August 2019) - Abdulrazak, S.; Marzouki, A.; Bah, S.T.; Lahrach, K.; Boutayeb, F.
Abstract: Background: Giant cell tumours are common primary long bone tumours with femoral neck locations infrequent and notorious for pathological fractures. Treatment with simple curettage often results in local recurrence. Aggressive treatment that combines tumour resection with cement filling and internal fixation aims at preserving native joint function. Case report: The authors intend to illustrate the short falls of such conservative approach through a case report of a femoral neck giant cell tumour in a 37 year old patient. Patient had undergone curettage-cavity filling with screw fixation for a pathological femoral neck fracture. Total hip arthroplasty was undertaken following implant failure and severe hip impairment 3 years after initial surgery. Conclusion: Intralesional curettage and cavity cementation with internal fixation of giant cell tumour of the proximal femur allows joint preservation. Mechanical failure, local recurrence and degenerative changes hinder long term outcomes especially in the setting of pathological fractures. Further studies are required to delineate the benefits of joint sparing techniques vis-a-vis total hip replacement for giant cell bone tumours of the femoral neck.